2005
DOI: 10.1007/s10943-005-2772-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Beliefs and Barriers Among Managed Care Practitioners

Abstract: Managed care practitioners in a time constrained setting were spiritual themselves and believed this to be important to patients. Respondents indicated barriers of time and training to implementing these beliefs. Comparing responses from our group to those in other published surveys on clinician spirituality, we find similar concerns. Clinician education may overcome these barriers and improve ability to more fully meet their patients' expressed needs regarding spirituality and beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
1
23
0
5
Order By: Relevance
“…Most common was insufficient time. 9,18,28,30,33,36,[43][44][45][46][49][50][51]57,59,62,69,73,79,82,83 However, when Ellis and colleagues 6 looked at frequency of spiritual interactions between physicians and their hospitalized patients, there was no difference in conversation frequency between standard and 'step-down care' hospitals, despite the longer length of stay (average >11 days) at the latter. Resident doctors in another study did not mention time as a barrier so much as a factor to be managed.…”
Section: What Are the Known Barriers To Doctors Asking Their Patientsmentioning
confidence: 99%
“…Most common was insufficient time. 9,18,28,30,33,36,[43][44][45][46][49][50][51]57,59,62,69,73,79,82,83 However, when Ellis and colleagues 6 looked at frequency of spiritual interactions between physicians and their hospitalized patients, there was no difference in conversation frequency between standard and 'step-down care' hospitals, despite the longer length of stay (average >11 days) at the latter. Resident doctors in another study did not mention time as a barrier so much as a factor to be managed.…”
Section: What Are the Known Barriers To Doctors Asking Their Patientsmentioning
confidence: 99%
“…32 Although several studies have reported that patients rely upon religion, spirituality, and faith during times of need when coping with illness or injury, other studies have determined that those needs were unmet by both clergy and clinicians. 29,31,33,34 That may be a consequence of multiple factors, including the perceived biases, dichotomies, and prejudices of the sciences versus the humanities, the secular versus the sacred, the self versus the society, and the imperatives of the cure of disease versus the relief of suffering. Additionally, the ability, capacity, inclination, and volition of the patient, the clergy, and the clinician vis-à-vis religiosity and spirituality, and its role in the delivery of health care, may be operative.…”
Section: Introductionmentioning
confidence: 99%
“…A falta de treinamento e de habilidade em identificar as demandas dos usuários, assim como o receio de influenciar as crenças dos pacientes, constituem barreiras percebidas pelos próprios profissionais, que dificultam a abordagem da religiosidade/espiritualidade nos atendimentos (Balboni et al, 2007;McCauley et al, 2005;Monroe et al, 2003).…”
Section: Religiosidade E Espiritualidade No Contexto Oncológicounclassified
“…Em contraponto, diversos estudiosos ressaltam benefícios da religiosidade/espiritualidade para o enfrentamento de doenças, justificando a inclusão da temática nas intervenções em saúde (Balboni et al, 2007;McCauley et al, 2005;Monroe et al, 2003;Panzini & Bandeira, 2007;Saad, Masiero, & Battistella, 2001). Para alguns autores, isto propicia a compreensão das crenças dos pacientes e sua relação com a doença, permitindo detectar interferências negativas na adesão aos tratamentos (Koenig, 2006;Post, Puchalski, & Larson, 2000).…”
Section: Religiosidade E Espiritualidade No Contexto Oncológicounclassified
See 1 more Smart Citation